Kemampuan Menulis Cerita Pendek Berdasarkan Pengalaman Siswa Kelas Ix A Smp Negeri 17 Kota Jambi Tahun Ajaran 2016/2017 - Risma Mawadah (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2017)
ABSTRACT The purpose of this study is to describe how the ability of students in writing short stories based on the experience of students of class IX A SMP Negeri 17 City of Jambi Academic Year 2016/2017. From the results of data processing is known short story writing based on the experience of students of class IX A SMP Negeri 17 17 City of Jambi berkriteria quite capable (CM). This is proven by obtaining the average value of the appraiser 1 and appraisal 2 of 63.2 value is seen from the table of percentage calculation is at intervals of 56-74 with adequate criteria (CM). In detail the value is obtained from the elements of the formation of short stories, the theme selection with an average value of 62.7 with enough criteria (CM), the mandate to obtain an average value of 49.3 criteria less able (KM), plot description / plot obtained an average score of 80 capable criterion (M), the figures scored average of 60.7 with sufficient criteria (CM), background description earned an average of 86.3 highly qualified (SM) scores, the average score of 46 criteria for underprivileged (KM), and the drawing for the point of view obtained an average rating of 57.3 with sufficient criteria (CM). Keywords: Write a short story